(untitled) (Orthodontic Journal of Nepal, 2020)
Introduction: To investigate the quality of information offered by videos on YouTube™ for those individuals seeking information regarding risks associated with orthodontic treatment. The quality of information was compared the British Orthodontic Society (BOS) patient information leaflet ‘Orthodontic treatment- what are the risks’. Materials and Method: YouTube™ was searched systematically for videos on orthodontic treatment risks using the terms ‘orthodontic risks’ and ‘braces risks’. Videos were selected based on a strict inclusion and exclusion criteria and demographics recorded. Completeness was assessed using a 8-point score based on the BOS patient information leaflet ‘Orthodontic treatment- what are the risks’. Descriptive statistics and statistical analysis using correlation tests were generated. Result: 19.2% videos met the specified criteria with 80.8% videos excluded. Videos varied in regards to completeness with the mean completeness score of 3 and only 13% meeting all criteria. The risk of pain and discomfort was most commonly included orthodontic risk 61%. No statistical significance was found for completeness of the video with viewers interaction (R = 0.2665, P=0.219897) viewing rate (R=0.1138, P=0.617326) or length of video (R=0.0062, P= 0.977601). Conclusion: YouTube™ generally hosts videos with low completeness with regards to orthodontic treatment risks. Therefore, orthodontists should be aware of this resource and caution patients regarding the comprehensiveness of information. In addition to the potentially misleading content which is avail-able within YouTube™ videos